2016
DOI: 10.1007/s10840-016-0181-y
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial lead fixation type and lead position are associated with significant variation in complications

Abstract: Active compared to passive lead fixation increases the risk for pericardial effusion requiring pericardiocentesis. There is a clear association between low atrial septal lead position and lead dislodgement requiring lead revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…The active fixation leads, with a screw‐in mechanism, conceptually were purported to provide more consistent contact with myocardial tissue and prevent dislodgement, thus leading to a lower incidence of high pacing threshold or loss of capture events. One‐year follow‐up data from Witt et al . showed that lead dislodgement in the active fixation method was similar to that in passive fixation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The active fixation leads, with a screw‐in mechanism, conceptually were purported to provide more consistent contact with myocardial tissue and prevent dislodgement, thus leading to a lower incidence of high pacing threshold or loss of capture events. One‐year follow‐up data from Witt et al . showed that lead dislodgement in the active fixation method was similar to that in passive fixation.…”
Section: Discussionmentioning
confidence: 91%
“…These studies included 17,321 patients undergoing conventional single‐ or dual‐chamber PM implantation (Figure ; Table ) and 2,046 patients for a LCP device (Table ). Of the identified studies, only one was a randomized controlled clinical trial, whereas the remainder were post hoc analyses of randomized trials, or observational retrospective or observational prospective studies . The vast majority were multicenter studies, with seven single‐center studies .…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, many people think that this position is very thin, and it is easy to cause perforation when xing the electrode. However, there is no signi cant difference in postoperative complications (such as perforation, pericardial effusion, dislodgement), pacing sensing, pacing threshold and impedance [14][15] . In addition, the use of active atrial lead xation can reduce the incidence of dislodgement [16][17] , and signi cantly reduce the bed rest time and duration of hospital stay of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pericardial effusion and pericardiocentesis with active fixation leads in the atrium is higher than that with passive fixation leads because of the thin free wall. 15 However, a good percepual and pacing function of the atrial lead are important for patients with sick sinus syndrome with an indication for pacemaker implantation. Considering the anatomical specificity of this patient, we decided to use active fixation leads in the right atrium to reduce the incidence of dislodgement.…”
Section: Discussionmentioning
confidence: 99%